The Effect of Organizational Virtuousness on Employees’ Innovative Behavior: The Role of Moderating and Mediating Variables - Sabti, Yousif Mousa; Hisnawi, Salih M AL; AlMousawi, Kawthar Mowaffak Jaber; Radhi, Aeshah Hasan (South Asian Journal of Social Sciences and Humanities, 2024)
This objective of the study is to assess the association between OV and IB. Furthermore, the study scrutinizes the mediating effect of thriving between OV and IB. Moreover, this study also examines the moderating effect of CSE between thriving and IB. A quantitative also cross sectional design was used. Data was collected from to test the proposed 509 respondents from high-tech construction and manufacturing industries of Iraq. The findings shown that OV has a positive association with innovative behavior. The mediation result also was significant. The findings shown that CSE weakened the association between thriving and IB. In the end, theoretical and practices implications was discussed with future recommendation.